2021
DOI: 10.3389/fonc.2021.574774
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factor of Large‐Volume Central Lymph Node Metastasis in Clinical N0 Papillary Thyroid Carcinoma Patients Underwent Total Thyroidectomy

Abstract: Large‐volume central lymph node metastasis (large-volume CLNM) is associated with high recurrence rate in papillary thyroid carcinoma (PTC) patients. However, sensitivity in investigating large-volume CLNM on preoperative ultrasonography (US) is not high. The aim of this study is to investigate the clinical factors associated with large-volume CLNM in clinical N0 PTC patients. We reviewed 976 PTC patients undergoing total thyroidectomy with central lymph node dissection during 2017 to 2019. The rate of large-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Age is important for PTC staging. Traditionally, patients over 45 years of age have a slightly worse prognosis and an increased recurrence rate ( 13 , 14 ). Some studies have also shown that age is a risk factor for central CLNM.…”
Section: Introductionmentioning
confidence: 99%
“…Age is important for PTC staging. Traditionally, patients over 45 years of age have a slightly worse prognosis and an increased recurrence rate ( 13 , 14 ). Some studies have also shown that age is a risk factor for central CLNM.…”
Section: Introductionmentioning
confidence: 99%
“…These are consistent with the conclusion from the analysis of the relationship between tumour size and LNM in our meta‐analysis. However, among the included 11 articles, only three (including our data) supported that tumour diameter greater than 0.5 cm was an independent factor affecting hv‐CLNM, 35,40 while five studies did not 31,32,34,36,37 . Combined with the findings of our meta‐analysis, we believe that the results of these five studies were influenced by a small number of positive cases.…”
Section: Discussionmentioning
confidence: 47%
“…Subsequently, the full text was carefully read and three papers on the analysis of PTC were excluded as PTMC subgroup analysis was not performed; one of these did not provide the available data and was excluded. Finally, 11 studies that met the inclusion criteria comprising 14,002 patients (including our data) were included in the meta‐analysis 31–40 . The incidence of hv‐CLNM in the literature ranged from 3.4% to 9.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Age is the most important prognostic factor for thyroid carcinoma [9]. Large-volume LNM is more likely to appear in PTMC patients aged <40 years [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that age (<40 years old) and male sex were significantly associated with large-volume LNM in PTC patients [9][10][11]. Nevertheless, these studies focused on identifying risk factors for large-volume LNM rather than constructing a predictive model.…”
Section: Introductionmentioning
confidence: 99%